Journey(s) to the East-travels, trajectories, and transnational Chinese theatre(s). - Ferrari, Rossella (Postcolonial Studies, 2010)
The notion of transnationalism represents a key theoretical paradigm in most contemporary studies of Chinese-language literature, film, and the visual arts. Scholarship in Chinese-language theatre, however, is still largely shaped by national or mono-regional patterns of analysis and criticism. This article attempts to update such a framework by proposing the concept of transnational Chinese theatre(s) and tracing the contours of an expanding field of trans-Chinese/trans-Asian performance defined by collaborations and exchanges within and across the borders of Greater China-particularly in the realm of the avant-garde. The transnational and transmedial series Journey to the East (Zhongguo lucheng), created and coordinated by the Hong Kong arts collective Zuni Icosahedron, is examined as a paradigmatic illustration of this praxis. In the course of two decades Journey brought together artists and critics of Chinese (and subsequently Asian) descent hailing from several regions and disciplines to explore the potential of performance to establish alternative intellectual borders and new discursive bridges for artistic production and cultural dialogue. The concept of Journey rests upon fundamental notions of mobility, travel, and communication, and articulates an effort to map new relational trajectories and 'rhizomatic' paths. It highlights processes in which geopolitical, cultural, and transmedial boundaries are crossed, as well as questions of technology, tradition, and translation. It thus effectively voices the new transnational discourses and global demands of the Greater Chinese cultural field at the turn of the millennium. The analysis of this seminal project serves to outline the defining tropes and trajectories of transnational Chinese theatre(s), as well as its implications for the (re-)conceptualization of interculturalism and avant-garde theory in non-Western contexts.